Propuesta estratégica de posicionamiento que incremente la audiencia de Radio San Francisco en la ciudad de Cajamarca 2021 - Quispe Hoyos, Rosa Nathalie (2022)
Radio San Francisco is a radio station that has almost 4 decades at the service of the Cajamarquina population through the modulated transmission frequency. Being present in the market for so many years has implied a constant adaptation to the media, formats, listeners, among others, that the new generations bring with them, the new times. The current situation of the company is not the same as a few years ago in many aspects, the main one is the audience level, according to market measurements, Radio San Francisco has not been listed in the Top 5 of the most listened radio stations for years in the city of Cajamarca and this data turns out to be as important as it is worrying. Faced with this problem, this research seeks to identify the relationship between positioning and audience in order to determine which positioning strategies are that Radio San Francisco should apply in its management to improve its level of radio audience in the city of Cajamarca. The approach used is quantitative because “it is based on the collection of information that is mostly capable of counting or measurement, by means of rigorously validated instruments. The collected data are analyzed based on statistical methods and then proceed to test the hypothesis and draw conclusions” (Baptista et al., 2010). Finally, thanks to the exhaustive field work carried out where a questionnaire was applied to 388 respondents, it was possible to verify the relationship between audience and positioning, which led us to conclude that with adequate management and through specific strategies, Radio San Francisco can repower itself in the telecommunications market and being present in the Top 5 of the most tuned radio stations in the region.